2009
DOI: 10.1177/147323000903700336
|View full text |Cite
|
Sign up to set email alerts
|

Serious Antimicrobial Resistance Status of Pathogens Causing Hospital-acquired Lower Respiratory Tract Infections in North China

Abstract: Antimicrobial resistance patterns of pathogens causing hospital-acquired lower respiratory tract infections (LRTIs) in Shandong Province, China were investigated using data collected from January 2002 to December 2006. A total of 10 337 isolates were characterized in sputum samples from 39 920 LRTI patients: 68.72% were Gram-negative bacteria, 20.65% were Gram-positive bacteria, and 10.62% were fungi. Organisms most frequently isolated were: Pseudomonas aeruginosa (16.88%), Klebsiella pneumoniae (10.80%), Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The importance of regional specification of RTI and UTI etiology and their antibiotic susceptibility has been convincingly proved by several studies [5, 1318]. However, the knowledge needs to be regularly revised with changing trends in microbiological patterns of the responsible organisms [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of regional specification of RTI and UTI etiology and their antibiotic susceptibility has been convincingly proved by several studies [5, 1318]. However, the knowledge needs to be regularly revised with changing trends in microbiological patterns of the responsible organisms [15].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the trend has been different in 2007 with Pseudomonas aeruginosa being the most prevalent and Acinetobacter being the least frequent organisms. In a study by Wang et al from northern China, Pseudomonas aeruginosa was the most common isolated organism in hospitalized patients with lower respiratory tract infection [18]. However, a SENTRY antimicrobial surveillance program showed that Staphylococcus aureus comprised 28 percent of isolates followed by Pseudomonas aeruginosa in 20.0 percent, Streptococcus pneumonia in 9.1 percent, and Klebsiella saprophyticus in 7.5 percent among hospitalized patients in northern America and Canada [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas showed resistance to imipenem (19.4%), ceftazidime (28.1%), cefaperazone (33.7%), ciprofloxacin (71.8%), of loxacin (63.8%) and ampicillin (90.7%). 11 Among the eight positive blood samples five enterococci and three staphylococcus aureus were isolated. Enterococci showed sensitivity to vancomycin, gentamycin, ciprofloxacin, chloramphenicol, linezolid and amikacin.…”
Section: Resultsmentioning
confidence: 99%
“…2,8 Another study showed that in every tenth patient with community acquired pneumonia, etiology due to Gram negative bacteria had to be considered. 9 P. aeruginosa was the most commonly isolated organism of the Gram negative bacteria (32.1%).…”
Section: Discussionmentioning
confidence: 99%